Penerapan Sistem Informasi Pemerintah Daerah pada Badan Perencanaan Penelitian dan Pengembangan Daerah Kota Kotamobagu - Lumintang, Risca; Morasa, Jenny; Kindangen, Wulan Deisy (Yayasan Widyantara Nawasena Raharja, 2025)
The Regional Government Information System (SIPD) is a digital platform mandated by the Ministry of Home Affairs to improve the transparency and efficiency of regional development planning and financial management. This study aims to evaluate the implementation of SIPD at the Regional Development Planning and Research Agency (Bappelitbangda) of Kotamobagu City, focusing on how the system supports development planning and financial reporting. Using a qualitative descriptive method, data were collected through in-depth interviews with key informants, observation, and documentation. The findings reveal that despite SIPD's potential benefits in streamlining planning and budgeting processes, its implementation remains suboptimal due to limited human resource capacity and confusion regarding program nomenclature changes. As a result, the agency still frequently relies on the older SIMDA system. Theoretically, this research contributes to the literature on public sector accounting systems in developing countries. Practically, it underscores the need for enhanced training and system familiarization to ensure effective SIPD utilization. Further research is recommended to explore SIPD implementation across diverse types of regional agencies.